-7(y-2)=-2y+39

Simple and best practice solution for -7(y-2)=-2y+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(y-2)=-2y+39 equation:


Simplifying
-7(y + -2) = -2y + 39

Reorder the terms:
-7(-2 + y) = -2y + 39
(-2 * -7 + y * -7) = -2y + 39
(14 + -7y) = -2y + 39

Reorder the terms:
14 + -7y = 39 + -2y

Solving
14 + -7y = 39 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
14 + -7y + 2y = 39 + -2y + 2y

Combine like terms: -7y + 2y = -5y
14 + -5y = 39 + -2y + 2y

Combine like terms: -2y + 2y = 0
14 + -5y = 39 + 0
14 + -5y = 39

Add '-14' to each side of the equation.
14 + -14 + -5y = 39 + -14

Combine like terms: 14 + -14 = 0
0 + -5y = 39 + -14
-5y = 39 + -14

Combine like terms: 39 + -14 = 25
-5y = 25

Divide each side by '-5'.
y = -5

Simplifying
y = -5

See similar equations:

| 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t |

Equations solver categories